2021
DOI: 10.3390/antibiotics10091133
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antibiotic Resistance Profile of Bacterial Pathogens in Aerobic Vaginitis: A Retrospective Study in Italy

Abstract: Aerobic vaginitis (AV) is a vaginal infectious condition, characterized by a high inflammatory response and/or signs of epithelial atrophy, a decrease in the amount of Lactobacillus spp. and an increase in enteric origin bacteria. AV, often misdiagnosed, is difficult to treat due to the emerging spread of multi-drug resistant bacterial strains. The present study aimed to define the prevalence of AV, to detect causative bacteria and their antimicrobial resistance pattern. Women 10–95 years old, admitted to San … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
3
11
0
Order By: Relevance
“…Furthermore, our study found imipenem with the sensitivity of 84.6%, nor oxacin with 64.7% and nitrofurantoin with 61.2%. This nding was in concordance with Serretiello et al study [23] that found E. coli with high sensitivity to carbapenems and amikacin. Despite these antibiotics retaining their potencies against the isolated blood pathogens, the pathogens were slowing exhibiting resistances perhaps due to their over-use, and hence implementing effective antimicrobial resistance surveillance system such as antimicrobial stewardship programs and/or using the global antimicrobial resistance surveillance system(GLASS) should be considered by various hospitals [21].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, our study found imipenem with the sensitivity of 84.6%, nor oxacin with 64.7% and nitrofurantoin with 61.2%. This nding was in concordance with Serretiello et al study [23] that found E. coli with high sensitivity to carbapenems and amikacin. Despite these antibiotics retaining their potencies against the isolated blood pathogens, the pathogens were slowing exhibiting resistances perhaps due to their over-use, and hence implementing effective antimicrobial resistance surveillance system such as antimicrobial stewardship programs and/or using the global antimicrobial resistance surveillance system(GLASS) should be considered by various hospitals [21].…”
Section: Discussionsupporting
confidence: 93%
“…Thereafter, resistance data were interpreted according to EUCAST-2020 guidelines. The antimicrobial agents were tetracycline (30 μg), ampicillin (2 μg) ciprofloxacin (5 μg), gentamycin (10 μg), high-level gentamicin (30 µg) and (500 μg), high-level streptomycin (300 µg), erythromycin (15 μg), vancomycin (5 µg), clindamycin (2 μg), oxacillin (1 μg), penicillin G (1 μg), and kanamycin (30), (Oxoid, UK) [ 36 ]. Enterococcus faecalis ATCC 29,212, Staphylococcus aureus ATCC 25,923, and E. coli ATCC 35,218 were used for quality control for antimicrobial susceptibility testing [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…The European Centre for Disease Prevention and Control (ECDC) recognized neonatal infections as one of the six main types of healthcare-associated infections (HABSIs) in 2016 [ 1 ]. The first few months of neonatal life, especially the first month, are the main period of risk for child survival [ 2 , 3 ], whose mortality rate has increased approximately 50% due to preterm births or problems derived from childbirth. Although advances in obstetrics and technologies have minimized the number of birth-related problems, HABSIs pose different challenges in identifying the main factors affecting mortality and morbidity, which represent the main reason for mortality in children with a birth weight less than 1500 g in the Neonatal Intensive Care Unit (NICU) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%